Hip and Groin Pain in the Child Athlete - Broadley, Penny; Offiah, Amaka C. (Seminars in Musculoskeletal Radiology, 2014)
An increasing number of children are taking up sporting activities and at more competitive levels. For this reason (pediatric) radiologists should expect to receive greater numbers of requests from their orthopedic colleagues to image the athletic child who presents with hip or groin pain: “athletic pubalgia.”Lower limb sports-related pathology is particularly common in sports such as ballet, football, hockey, rugby, and running. Injuries to the hip and groin may account for up to a quarter of injuries seen in athletic children and may be acute or chronic, osseous, cartilaginous, ligamentous, or muscular. The radiologist should also bear in mind the possibility of non–sports-related pathology such as inflammation or tumor and of complications related to previous trauma such as avascular necrosis or femoroacetabular impingement complicating previous slipped capital femoral epiphysis. Radiologists should avoid use of the term sports hernia and provide a more specific description of the true abnormality.The major imaging modalities are radiographs and MRI. In this article we provide an overview of the common sports-related pathologies of the hip and groin that may be encountered in the athletic child.
Keywords: hip; groin; child; athlete; pain; sport injuries; athletic pubalgia